Efektivitas Model Problem Based Learning Berbantuan Media KIT IPA terhadap Kemampuan Berpikir Kritis Siswa - Izharifa, Febrisa Rifda; Fakhriyah, Fina; Masfuah, Siti (PGSD Universitas Muria Kudus, 2024)
The aim of this research is to analyze the average increase in students' critical thinking abilities before and after using the PBL model assisted by KIT IPA media. This type of research is pre-experimental with a one group pretest-posttest design. The sample in this study consisted of 23 fifth grade students at SD 6 Tanjungrejo. The sampling technique uses purposive sampling technique. The data collection techniques used in this research are tests and non-tests. The technical test is used to measure students' critical thinking abilities in the form of 10 essay questions. The non-test techniques used are interviews and documentation. The data analysis technique used in this research uses the n-gain test using SPSS 23 software which has previously been tested as a prerequisite in the form of a data normality test. The research results show that the n-gain percentage value is 67% in the medium category. Based on these results, there was an increase in students' critical thinking abilities after the PBL model assisted by KIT Science media was implemented.